Endotracheal Tube and Proseal Laryngeal Mask Airway in Elderly Hypertensive Diabetic Patients Undergoing Routine Laparoscopic Surgical Procedures: A Comparison of Hemodynamic Parameters - Rahman, Md Mushfiqur; Munir, Md Mhbubul Hasan; Sardar, Kawsar; Khan, Abdus Salam; Chowdhury, AKM Nurnobi; Rahman, Md Khalilur; Mondal, Samiron Kumar (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: The effects of ProSeal laryngeal mask airway (PLMA) removal and tracheal extubationon cardiovascular responses were studied in elderly hypertensive diabetic patients in a randomize double-blind study. Methods: A total of 60 elderly controlled diabetic hypertensive American Society of Anesthesiologists II & III patients were randomly allocated to two groups (n-30 of each) for PLMA insertion or endotracheal intubation. A standardized anesthetic sequence was used for induction and maintenance of anesthesia. The two groups were then compared for haemodynamic changes at the time of extubation/PLMA removal. Results: In PLMA group, heart rate increased during PLMA removal but remained elevated for only 3 minutes while mean arterial pressure remained elevated for only 2 minutes.The elevations of heart rate and mean arterial pressure were exaggerated in the extubation group and persisted for more than 5 minutes. No complication was observed in any patient and no difficulty was encountered in insertion of PLMA in any patient. Conclusion: Elderly hypertensive diabetic patients are at risk of exaggerated pressor response at the time of extubation. PLMA removal is associated with fewer hemodynamic changes than tracheal extubation and should be preferred wherever possible. J Bangladesh Coll Phys Surg 2018; 36(4): 153-158